1992
DOI: 10.1063/1.107364
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Raman and photoluminescence spectra of porous silicon

Abstract: The discovery of luminescence in electrochemically etched porous silicon is an extremely important scientific breakthrough with enormous technological implications. It opens the door for silicon, the most important microelectronic material, as a possible material for optoelectronics applications. Our result, a correlation of Raman and photoluminescence spectra, shows that the observed luminescence is originated from extremely small microstructures. As the luminescent peak increases in photon energy, the Raman … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
66
0
1

Year Published

1995
1995
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 263 publications
(70 citation statements)
references
References 9 publications
3
66
0
1
Order By: Relevance
“…the origin of two bands between this band and 520 cm 1 (bulk phonon wavenumber) is due to a splitting of the optical phonon (degenerate for q D 0 in the Brillouin zone center) in transverse (TO) and longitudinal (LO) modes for larger q-values, 55 to a combined contribution of two types of nanocrystallites 36,41,43,56 or to a shell structure of the particles with modified vibrational contributions of the near-surface atoms. Xia et al 51 observed in hydrogenated nanocrystalline Si films one band for crystalline sizes L Ä 2.2 nm and L ½ 5.3 nm.…”
Section: Size Determination By Raman Scatteringmentioning
confidence: 99%
“…the origin of two bands between this band and 520 cm 1 (bulk phonon wavenumber) is due to a splitting of the optical phonon (degenerate for q D 0 in the Brillouin zone center) in transverse (TO) and longitudinal (LO) modes for larger q-values, 55 to a combined contribution of two types of nanocrystallites 36,41,43,56 or to a shell structure of the particles with modified vibrational contributions of the near-surface atoms. Xia et al 51 observed in hydrogenated nanocrystalline Si films one band for crystalline sizes L Ä 2.2 nm and L ½ 5.3 nm.…”
Section: Size Determination By Raman Scatteringmentioning
confidence: 99%
“…This has been proposed and explained by phonon confinement model [13]. Confinement of phonons for Si, Ge, BN, CdS, CdS x Se 1−x and many other nanocrystals have been reported in the literature [14,15,16,17,18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the observed increase in the amount of PL blue shifting to lower wavelengths, over the current densities of 20-90 mA/cm 2 should be also caused by decreasing Si nanocrystallite size, resulting in an increased surface-induced residual stress (lateral stress), causing a smaller lattice mismatch, compared with c-Si substrate. [19][20][21]36 Whereas, observed slight decrease in the PL blue shifting at the current density of 100 mA/cm 2 can be explained in terms of slightly larger Si crystallite size, causing a slightly larger lattice mismatch at Si-PS interface, induced by larger residual stress (both lateral and vertical stress) with respect to those of the PS sample of 90 mA/cm 2 . of the Si nanocrystallite size (or porosity) and the residual stress, due to the applied current density.…”
Section: 3mentioning
confidence: 99%
“…According to the QCE, the average size of nanocrystallites in PS is expected to get smaller and make a blueshift in PL peaks, with the increasing applied current density. 1,10,11,14,29,31,36 Based on the origin of the luminescence, this blueshift increase should be resulting from the quantum-sized silicon crystallites among the walls, or from the defect and the species formed during the anodization process in Si complexes including amorphous silicon, siloxene and Si hydrides.…”
mentioning
confidence: 99%